The Little Data Book on Gender 2013 - World Bank (Washington, DC, 2013)
The Little Data Book on Gender 2013 is a quick reference for users interested in gender statistics. It presents gender-disaggregated data for more than 200 countries in a straightforward, country-by-country reference on demography, education, health, labor force, political participation, and the Millennium Development Goals. Summary pages that cover regional and income group aggregates are also included.